Method for manufacturing battery cell
By using permanganate anions in the lithium-ion battery cell to form organic SEI and CEI layers in the chemical reaction of permanganate anions with organic polymers, the problems of reduced conductivity and increased impedance caused by large particles of SEI and CEI layers are solved, and the problem of reduced conductivity and increased impedance caused by large particles of SEI and CEI layers is achieved. Higher lithium ion mobility and lower cell impedance.
Patent Information
- Application Number
- CN202411119667.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-17
- Filing Date
- 2024-08-15
- Publication Date
- 2025-02-21
AI Technical Summary
Large particles of the SEI and CEI layers in the lithium-ion cell lead to a decrease in the conductivity of lithium ion, poor adhesion between the organic and inorganic components of the SEI layer leads to rupture of the SEI layer, and the thickness of the CEI layer increases with the charging operation, resulting in the cell The impedance increases.
Using a method of manufacturing a battery cell, by filling a first electrolyte with an organic polymer, the electrolyte comprising an organic polymer, and wetting the anode and cathode material by a first electrolyte, and then further filling the housing with a second electrolyte , the second electrolyte contains at least a permanganate anion. This method forms organic SEI and CEI layers on the anode and cathode through the chemical reaction of permanganate anion with the organic polymer, thereby preventing strong adhesion of the inorganic layer, thereby controlling the thickness of the CEI layer.
By forming SEI and CEI layers with small grain sizes, the mobility of lithium ions is improved, the impedance and internal resistance of the battery cell are reduced, the adhesion of the SEI layer is enhanced, and the dissolution of the organic layer and the thickness of the inorganic layer is increased. .
Smart Images

Figure CN119495827A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a battery cell. In particular, the method relates to the replacement manufacturing of a SEI or CEI layer on an anode or cathode of a battery cell. Background Art
[0002] Batteries, especially lithium-ion batteries, are increasingly used to drive motor vehicles. Batteries usually consist of battery cells, each of which has a stack of anode, cathode and separator layers. At least a portion of the anode and cathode layers is designed as a current conductor for conducting the current provided by the battery cell to a load arranged outside the battery cell. The battery cell also includes an electrolyte.
[0003] During the first charging process (formation) of the battery cell, the so-called SEI (solid electrolyte interface) forms on the boundary phase between the anode and the electrolyte, and the so-called CEI (cathode electrolyte interface) forms on the boundary phase between the cathode and the electrolyte. Thus, the SEI forms on the surface of the anode carrying the electrolyte, and the CEI forms on the surface of the cathode carrying the electrolyte.
[0004] During the subsequent charging process of the lithium-ion battery cell, lithium ions must first migrate through the SEI (solid electrolyte interphase) before being deposited in the active anode material. The lithium ions move along the grain boundaries of the SEI instead of passing through the particles. When the grain size of lithium ions is larger, lithium ions must travel a longer distance along the grain boundaries to move to another subsequent grain boundary. Each longer displacement of lithium ions reduces the conductivity of lithium ions, thereby increasing the internal resistance of the battery cell.
[0005] Typically, the radius of a lithium ion is about 90 pm (picometer), which is equivalent to about 1 Å [angstrom]. On the other hand, the thickness of the SEI is about 20 to 50 nanometers. Since lithium ions cannot pass directly through SEI particles, but can only move along grain boundaries, they must travel a longer distance than the thickness of the SEI. For larger SEI particles, the displacement along the grain boundaries becomes longer, so lithium ions may have to travel more than five times the thickness of the SEI. However, this means that lithium ions must travel a distance of 1000 Å to 2500 Å, which is about 1000 times the radius of the lithium ion. If the particles of the SEI layer are smaller, there will be more grain boundaries and more possibilities for lithium ions to transfer within the SEI.
[0006] The SEI is a three-dimensional boundary layer built around the active anode material (e.g. graphite). Every crack in the anode material opens up a new surface on which the SEI can accumulate. These SEI accumulations increase the electrical resistance and also reduce the ionic conductivity in the battery cell. The SEI layer consists of multiphase compounds. The SEI near the active anode material is mainly inorganic compounds such as LiF, Li2O, lithium carbonate and lithium hydroxide. These are formed by the reaction of lithium cations (derived from lithium salts) with fluoride anions (derived from lithium salts) or oxygen (derived from trace amounts of water). Due to its dense layer, this (inorganic) part of the SEI has a higher resistance to the movement of ions. In the area close to the electrolyte (i.e. on the side of the SEI facing away from the active anode material), the SEI is mainly formed by organic compounds, for example from the reaction products of solvents such as ethylene carbonate (EC) or (additionally) vinylene carbonate (VC). These organic compounds react with HF acid and are then converted over time into the organic layer of the SEI. This means that the resistance of the SEI layer increases over time. Currently, there is no way to increase the ionic conductivity and reduce the SEI impedance (the resistance of the SEI).
[0007] Among the inorganic components of SEI, that is, the part of SEI formed close to the anode material, lithium is responsible for the preparation of compounds such as LiF, Li2O and Li2CO3.
[0008] The organic components of the SEI are mainly formed by the reduction of the electrolyte and do not form compounds with lithium. The organic components mainly consist of polyolefins. They have poor adhesion to the inorganic components or layers or active materials of the anode. This part of the SEI, the organic component of the SEI, can already be separated under vibrations and / or high temperatures. In particular, at temperatures exceeding 70°C [degrees Celsius] and in the case of strong vibrations, this organic layer or component may break. In fact, organic SEI components have lower lithium ion conductivity than inorganic SEI components (especially those based mainly on fluorides). The problem is that if the inorganic layer becomes thicker with each (charge / discharge) cycle, this will increase the impedance and internal resistance of the battery cell.
[0009] Just as the SEI is formed on the anode side by the reduction of the electrolyte, the CEI is formed on the cathode side in a similar manner by the oxidation of the electrolyte on the cathode surface. The CEI consists mainly of inorganic components such as Li2O and LiF. The thickness of the CEI increases with each cycle (charge / discharge operation of the battery cell), which leads to an increase in the internal impedance (resistance) of the battery cell. It is also important that the CEI has a smaller grain size and therefore an increased number of grain boundaries. In addition, it would be better if the organic layers were arranged between the inorganic layers so that thicker and thicker inorganic layers would not form. Due to the low adhesion between the inorganic and organic layers, the layers would separate from each other even in the case of slight vibrations, or the organic layer would dissolve faster, with the result that the thickness of the CEI layer would decrease. The organic layer is intended to reduce the cohesive forces between the inorganic layers. Therefore, the CEI layer always remains thin, i.e., less than 20 nm (nanometers) thick.
[0010] Therefore, there are three problems in particular:
[0011] 1. Large particles in the SEI and CEI layers lead to reduced lithium ion conductivity;
[0012] 2. Destruction of the SEI layer due to reduced adhesion (cohesion) between the organic and inorganic components of the SEI; and
[0013] 3. As the charging operation progresses, the thickness of the CEI layer gradually increases, and the impedance of the battery cell increases accordingly.
[0014] To solve these problems, the following measures are known:
[0015] · Use of additives such as vinylene carbonate in the electrolyte. Ethylene carbonate forms the SEI by reduction on the anode side much earlier than the solvent of the primary electrolyte forms the SEI. Vinylene carbonate reduces the amount of SEI formed on the anode surface because the solvent of the primary electrolyte can no longer directly contact the anode surface. For example, when the voltage applied to the battery cell is 1 volt or less, the primary electrolyte decomposes. Vinylene carbonate is reduced at higher voltages. For example, solvents such as ethylene carbonate (EC) form SEI at 0.2 to 0.7 volts relative to Li / Li+. Vinylene carbonate (VC) forms between 0.8 and 1.1 volts relative to Li / Li+. This means that the SEI is established earlier with VC than with EC. In this way, the SEI is established earlier and prevents the contact of the primary electrolyte solvent, such as ethylene carbonate or propylene carbonate (PC), with the anode surface. CEI is constructed on the cathode by sulfur-based additives such as PS, ES, PES, and DDT. They form CEI on the cathode by oxidation before the solvent oxidizes EC or PC.
[0016] Higher impedance due to thicker SEI and CEI layers is acceptable.
[0017] However, these known measures have the following disadvantages:
[0018] 1. The cost of electrolyte is high, and the electrolyte must contain additives such as vinylene carbonate or sulfur-based additives;
[0019] 2. As SEI thickness increases, ion mobility decreases;
[0020] 3. The impedance of the battery cell increases with the increase of CEI thickness.
[0021] US2018 / 0233784 A1 discloses an alkali metal sulfur secondary battery with a nanosulfur-loaded cathode and a method for manufacturing the same. Summary of the invention
[0022] The technical problem to be solved by the present invention is to at least partially solve the problems mentioned with reference to the prior art. In particular, a method for manufacturing a battery cell is proposed.
[0023] A method for producing a battery cell contributes to solving these problems. The features listed individually in the present application can be combined with one another in a technically reasonable manner and can be supplemented by explanatory facts from the description and / or details from the drawings, in which further embodiment variants of the invention are shown.
[0024] A method for producing a battery cell is proposed. The battery cell comprises a housing filled with an electrolyte and a stack of cathode material, anode material and separator material arranged therein. The method comprises at least the following steps:
[0025] a) providing a battery cell, the battery cell comprising the housing and (at least one) stack arranged therein consisting of (at least) a cathode material, an anode material and a separator material;
[0026] b) at least partially filling the housing with a first electrolyte, wherein the first electrolyte comprises at least an organic polymer; and thereafter
[0027] c) wetting the anode material and the cathode material with a first electrolyte; and thereafter
[0028] d) further filling the shell with a second electrolyte comprising at least permanganate anions.
[0029] The division of the above-mentioned (non-closed) method steps in a) to d) is mainly only used for differentiation, but not for mandatory order and / or dependency. The frequency of the method steps can also vary. The method steps can also overlap each other at least partially in time. Very particularly preferably, steps a) and b) occur in reverse order. In particular, at least steps a) to d) occur in parallel with each other in time. Step c) is especially carried out after steps a) and b). Steps b) to d) occur in particular in the order shown.
[0030] The battery cell comprises in particular a housing enclosing a volume and at least one cathode, an anode and a separator arranged between them arranged in the volume, and a liquid electrolyte. The cathode, anode and separator are in particular stacked on top of each other in a known manner. The terms cathode material, anode material and separator material refer to the cathode, anode and separator, respectively. The cathode material and the anode material each also comprise at least an active material.
[0031] The battery cells are in particular pouch cells (with a deformable housing consisting of a pouch film) or prismatic cells (with a dimensionally stable housing). The pouch film is a known deformable housing component that serves as a housing for so-called pouch cells. It is a composite material, for example comprising plastic and aluminum.
[0032] The battery cell is in particular a lithium-ion battery cell.
[0033] A battery cell is a current storage device, for example in a motor vehicle for storing electrical energy. In particular, for example, a motor vehicle has an electric motor for driving the motor vehicle (traction drive), wherein the electric motor can be driven by the electrical energy stored in the battery cell.
[0034] According to step a), a battery cell is provided, which comprises a housing and a stack of cathode material, anode material and separator material arranged therein. In step a), the battery cell also does not comprise an electrolyte.
[0035] According to step b), the housing is at least partially filled with a first electrolyte, wherein the first electrolyte comprises at least an organic polymer. In particular, the first electrolyte can also be arranged in the housing before stacking (i.e., step b) is performed before step a). In particular, the organic polymer only forms an additive for known electrolytes. Therefore, the first electrolyte particularly comprises a composition of different substances. The proportion of the organic polymer in the first electrolyte is particularly between 1 and 5% by volume, preferably at most 2% by volume.
[0036] For the first electrolyte, in particular, carbonate-based fast oxidizing and reducing organic compounds such as VC (vinylene carbonate), VEC (ethylene carbonate) or FEC (fluoroethylene carbonate) can be used, or inorganic materials such as DDT, PS, PES, ES, etc. based on sulfur and phosphorus, such as TMSP or nitrile, such as ADN or SN or LBOB (alone or in combination) based on boron. All of these materials oxidize much faster than solvents EC, DEC, DMC, PC or EMC and lithium salts such as LiPF6 or LiFSi or LiPO2F2. In addition, organic polymers account for about 2% by weight of the total amount of the first electrolyte and / or added electrolyte. These organic polymers can be easily oxidized, especially by chemical reactions with permanganates.
[0037] According to step c), the anode material and the cathode material are usually wetted with the first electrolyte. The aim here is to ensure that the anode and cathode materials are adequately acted upon by the first electrolyte.
[0038] According to step d), the housing is further filled with a second electrolyte comprising at least permanganate anions. In particular, the permanganate anions only form an additive to the known electrolyte. Therefore, the second electrolyte particularly comprises a combination of different substances. The proportion of permanganate anions in the total electrolyte added is particularly between 0.01 and 2% by weight, preferably between 0.8 and 1 (1)% by weight. The proportion of permanganate anions in the second electrolyte is particularly between about 0.02 and 0.7% by weight, preferably between about 0.2 and 0.3% by weight.
[0039] In particular, the proportion of permanganate anions is selected such that the remaining part of the organic polymer added to the first electrolyte can be oxidized.
[0040] In particular, the second electrolyte does not contain other additives contained in the first electrolyte. In particular, it contains only a solvent in the form of acetonitrile, which dissolves materials containing permanganate anions and salts, such as LiFSi.
[0041] The proportion of the second electrolyte in the total amount of electrolyte added (ie the sum of the first electrolyte and the second electrolyte) is in particular between 10 and 30% by volume, preferably between 15 and 25% by volume.
[0042] In particular, the first electrolyte comprises conventional components of electrolytes suitable for lithium battery cells and an additional organic polymer. The organic polymer serves in particular as a reactant for the permanganate anion.
[0043] The first electrolyte and the second electrolyte may have the same or different components except for the components of the organic polymer and the permanganate anion.
[0044] In particular, the second electrolyte (additionally) comprises at least potassium cations or sodium cations. The ratio of cations in the second electrolyte corresponds in particular (at least approximately) to the ratio of permanganate anions.
[0045] In particular, permanganate anions and cations are provided in a step d0) prior to step d), wherein at least potassium permanganate or sodium permanganate is mixed with a solvent and forms a solution. In this case, potassium permanganate or sodium permanganate is especially converted into permanganate anions and potassium or sodium cations.
[0046] In particular, the second electrolyte includes potassium permanganate or sodium permanganate dissolved in solution.
[0047] The solvent preferably contains at least acetonitrile.
[0048] In particular, between steps c) and d), the battery cell is connected to an external voltage source and the formation process is started, wherein the formation is carried out at a C-rate of at most 0.35C, preferably at most 0.2C, particularly preferably at most 0.1C.
[0049] The C-rate describes the charge (or discharge) current of a battery cell relative to its capacity. So, for example, if the capacity of a battery cell is 1,000 mAh [milliampere-hours], a C-rate of 1 or 1C would correspond to 1,000 mA [milliamperes] respectively. 0.5C would be 500 mA.
[0050] Of course, the formation process of the battery cell is basically known. In this case, a formation process is proposed, wherein the formation is carried out at a (than usual) lower C-rate.
[0051] In particular, a specified C-rate (e.g., at most 0.35C) is used for formation and for charging and discharging. The first cycle of formation (charging and discharging) is particularly carried out at a maximum of 10% SOC. Alternatively, when a specified SOC (e.g., at most 10% SOC) is reached, the second electrolyte can be added (i.e., without discharging). The first cycle of formation is particularly carried out under vacuum.
[0052] After the addition of the second electrolyte, in particular further (complete) formation takes place.
[0053] In particular, step d) is only performed when the battery cell has reached a state of charge of at least 1% and at most 10%, in particular between 2% and 8%.
[0054] The reason for this is, inter alia, that at this SOC at least a large part of the additives (e.g. based on carbonates, sulfur, phosphorus, nitrile or boron) supplied with the first electrolyte have already formed the SEI or CEI. In particular, the organic polymer is selected such that it is not oxidized by the selected maximum SOC and therefore remains unchanged during the first formation process. The organic polymer is oxidized by the permanganate anions of the second electrolyte.
[0055] In particular, only after step d) the C-rate is increased to a higher value of at least greater than 0.3 C. In particular, before step d) the C-rate is at most a certain value, and after step d) a different C-rate is set having a value higher than the determined value.
[0056] In particular, the active material of the anode includes at least graphite and hard carbon.
[0057] In particular, after step d), the permanganate anions react with the organic polymer to form an organic SEI layer on the anode material and an organic CEI layer on the cathode material.
[0058] In particular, when the second electrolyte is added, this reaction with the permanganate anion takes place immediately. The process is completed in particular in the second formation process. In particular, the organic polymer is completely oxidized. When the organic polymer is bound to the cathode, it forms oxidation products in particular at the cathode. When the organic polymer is located at the anode, it is oxidized at the anode. The oxidation of the organic polymer takes place in particular only by the permanganate anion. In particular, the organic polymer is not reduced or oxidized by the electrode voltage at the anode or cathode like other organic and inorganic additives.
[0059] In particular, after step d), the cation (or cation pair) of the permanganate anion reacts with (at least) one halide, thereby forming an inorganic SEI layer on the anode material.
[0060] In particular, after step d), in step e) the halide is added to the electrolyte arranged in the housing.
[0061] In particular, the method aims to form an organic CEI layer on the active material of the cathode without forming a thicker inorganic CEI layer. The organic layer prevents strong adhesion of the inorganic layer, thereby preventing the inorganic layer from increasing in structure (and thus preventing an increase in CEI thickness).
[0062] The organic layer is formed in particular by oxidation of electrolyte solvents, such as cyclic and acyclic solvents, which occurs at a high positive voltage at the cathode. However, this oxidation process of the solvent cannot currently be controlled.
[0063] It is therefore advisable to add very strong oxidizing agents, such as potassium permanganate (KMnO 4 ) or sodium permanganate (NaMnO 4 ; the statements made below regarding potassium permanganate apply in particular in the same way to sodium permanganate), to the electrolyte.
[0064] Potassium permanganate causes oxidation of some organic solvents in the electrolyte (electrolyte solvent), thereby forming oxidation products such as ketones, aldehydes and carboxylic acids, which remain attached to the active material at the cathode. In this way, oxidation is intentionally induced before oxidation of the solvent (or other solvents) occurs (caused by different conditions, i.e., by a high positive voltage at the cathode).
[0065] Then, the electrolyte solvents such as cyclic and non-cyclic carbonates are no longer oxidized because the organic layer of CEI is formed earlier by oxidizing organic additives such as alcohols with a strong oxidant, potassium permanganate.
[0066] The oxidation induced by potassium permanganate also leads to the formation of an organic SEI layer on the anode.
[0067] Potassium permanganate is reduced during the reaction to form manganese oxide. This manganese oxide forms part of the cathode active material. The manganese oxide forms a spinel material that helps lithium ions insert into the cathode during discharge, just like other cathode materials.
[0068] The oxygen released by potassium permanganate oxidizes the organic polymer (added as an additive to the first electrolyte) and forms an oxidation product such as a carboxylic acid, an aldehyde or a ketone.
[0069] During charge and discharge, an organic (SEI and CEI) layer is formed on the anode and cathode, respectively. In particular, it is entirely produced by the chemical reaction (oxidation) of the organic polymer by the permanganate anion.
[0070] Potassium cations inserted and absorbed in the active material of the anode (e.g., hard carbon) contribute to the formation of an inorganic SEI layer by reacting with fluoride anions of a lithium salt (e.g., lithium hexafluorophosphate). Bromide or chloride (e.g., a bromide- or chloride-containing salt such as lithium tetrafluoroborate or lithium perchlorate) may also be added to the electrolyte (in addition) so that the halide forms an inorganic potassium bromide or potassium chloride layer.
[0071] Bromide can also be added to the (first or second) electrolyte in the form of a salt, such as lithium tetrafluoroborate (LiBF4). Chloride can be added to the (first or second) electrolyte as a lithium salt, such as lithium perchlorate (LiClO4).
[0072] This potassium halide (also called potassium halide) (i.e. potassium fluoride, potassium bromide or potassium chloride) forms an inorganic SEI layer, especially before the organic SEI layer is formed by reducing the solvent of the electrolyte. This inorganic layer helps lithium ions pass through the SEI layer faster because the inorganic potassium halide layer is fine-grained and the formation of the SEI layer can be controlled in particular by the concentration of cations (potassium) and anions (halides).
[0073] In this way, potassium permanganate, especially together with other electrolyte additives (bromide / chloride and easily oxidizable organic polymers), can be particularly helpful in making fine-grained organic CEI and inorganic / organic SEI. The CEI or SEI is especially prepared before forming an organic or inorganic layer (such as other conventional ones) on a lithium base (i.e., by lithium).
[0074] In particular, only the additives added to the first electrolyte form SEI and CEI layers during the first formation, until, for example, a maximum SOC of 10% (i.e. before step d)). The SEI and CEI layers are then formed in particular (only) by reaction with permanganate anions. The electrolyte solvent in particular is not used to form the SEI or CEI. If no additional additives are added to the first electrolyte, in particular no SEI and CEI are formed during the first formation (i.e. before step d)). This means that the only SEI and CEI layers are formed by reaction of permanganate anions with organic polymers and lithium salts based on halogen anions.
[0075] In particular, a portion of the SEI and CEI is formed before the actual formation process of the battery cell begins (wherein an external voltage is first applied to the battery cell and the battery cell is first charged), or it may already be formed in an initial stage of formation, in particular before reaching, for example, a maximum of 10% SOC (state of charge).
[0076] The organic layer is therefore formed in particular not by oxidation induced by a cathodic voltage, but by the strong oxidizing agents potassium permanganate or sodium permanganate.
[0077] Potassium permanganate and sodium permanganate exist in crystalline form in particular and are easily soluble in water and other organic solvents. The permanganate anion is one of the strongest oxidants.
[0078] In particular, acetonitrile can be used as a suitable solvent for potassium permanganate or sodium permanganate. Acetonitrile has good solubility for potassium permanganate and sodium permanganate and is also a suitable electrolyte solvent. Acetonitrile can dissolve potassium permanganate or sodium permanganate but will not be oxidized. In particular, acetonitrile separates potassium permanganate or sodium permanganate into potassium cations or sodium cations and potassium permanganate anions.
[0079] Other solvents that can replace acetonitrile or be used alone or together as supplement to acetonitrile are for example diethyl ether and alkanes (pentane, hexane, cyclohexane) or some lower chlorinated hydrocarbons (methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane). Potassium permanganate or sodium permanganate are soluble in these organic compounds, but do not oxidize them. These solvents, particularly acetonitrile and diethyl ether, are preferred because they are also electrolyte solvents. These solvents decompose potassium permanganate or sodium permanganate into potassium cations or sodium cations and potassium permanganate anions.
[0080] In particular, polyethers (especially acrylic polyethers) can also be used as solvents and stabilizers for potassium permanganate or sodium permanganate. Polyethers can also be used as electrolyte solvents, so that potassium permanganate or sodium permanganate solutions are nothing more than potassium permanganate or sodium permanganate (about 0.1 to 0.2 moles) in organic and anhydrous electrolyte solvents (0.98 to 0.99 moles).
[0081] Therefore, potassium permanganate or sodium permanganate is provided in a solution and added to the battery as a component of the electrolyte to form the SEI or CEI layer. The solution comprising an organic solvent and potassium permanganate or sodium permanganate dissolved therein is in particular not added to the battery cell in the first electrolyte additive (first electrolyte), but is added to the battery cell in the subsequent second electrolyte additive (second electrolyte), in particular during the formation of the battery cell.
[0082] If potassium permanganate or sodium permanganate is supplied to the cell before the other electrolyte components are added, it oxidizes the active material of the anode and / or cathode, which is undesirable. By adding potassium permanganate or sodium permanganate, an organic layer is generated, in particular exclusively at the anode or cathode, from oxidation products, which layer is formed by oxidation of a suitable organic polymer with potassium permanganate or sodium permanganate. It is therefore particularly advantageous to first (as part of a first electrolyte addition) add the organic polymer to the cell and then (as part of a subsequent second electrolyte addition) add potassium permanganate or sodium permanganate or potassium permanganate or sodium permanganate dissolved in a solvent until the organic polymer can be oxidized.
[0083] After the addition of the first electrolyte (before step d)), in particular the first formation process occurs. In this case, an SOC of up to, for example, a maximum of 10% is formed. During this period, the above-mentioned additives added to the first electrolyte form SEI and CEI on the anode and cathode. In particular, organic polymers are neither reduced nor oxidized at the anode nor at the cathode because their LUMO is higher than the anode, while their HOMO is lower than the cathode. In particular, they only wet the anode and cathode electrodes. If a solution based on permanganate anions is added to the second electrolyte or input together with the second electrolyte, the solution only oxidizes the organic polymers covering the anode and cathode. As a result, an organic SEI or CEI layer is formed on the already existing SEI or CEI layer formed by the additives in the first formation process. These additives have been consumed, in particular in the first formation process (ie before step d)). Potassium and sodium cations also form inorganic layers by reacting with the halogens of lithium salts. Electrolyte solvents, such as EC, PC, etc., are not in direct contact with the electrodes in particular because they have SEI or CEI layers on the electrodes.
[0084] It should be noted that potassium or sodium permanganate can oxidize carbon atoms if they are present in a sufficiently weak bond, e.g.
[0085] 1. Carbon atoms with bonds, such as alkenes and alkynes;
[0086] 2. Carbon atoms with weak CH bonds, such as CH bonds at the α position of substituted aromatic rings, CH bonds in carbon atoms with CO bonds, including alcohols and aldehydes;
[0087] 3. Carbon with particularly weak C-C bonds, such as the C-C bonds in ethylene glycol, C-C bonds next to aromatic rings, and oxygen.
[0088] Potassium permanganate or sodium permanganate also oxidizes phenol to give p-benzoquinone. The action of potassium permanganate on alkylbenzenes results in oxidation to form benzoic acid.
[0089] Organic molecules are completely oxidized by potassium or sodium permanganate, in particular until carboxylic acids are formed. Thus, alcohols are oxidized to carbonyls (aldehydes and ketones), and aldehydes (and some ketones, as described in 3 above) are oxidized to carboxylic acids.
[0090] In particular, a number of organic polymers that oxidize very efficiently in the presence of potassium permanganate or sodium permanganate can be used. Such organic polymers oxidized by potassium permanganate or sodium permanganate form organic layers of the SEI and CEI before the electrolyte forms the SEI and CEI. Such organic polymers (not yet oxidized by potassium permanganate or sodium permanganate) are added to the cell as part of the first addition of electrolyte. Recommended organic polymers are weak acids, long chain alcohols, olefins and alkynes.
[0091] In particular, suitable organic polymers have a LUMO (Lowest Unoccupied Molecular Orbital) above the Fermi energy of the anode and a HOMO (Highest Occupied Molecular Orbital) below the Fermi energy of the cathode. This means in particular that they are not reduced or oxidized by the voltage on the anode and cathode. They can in particular only be oxidized by strong oxidants such as permanganate anions.
[0092] Therefore, in order to produce a battery cell, a housing of the battery cell and a stack of anode, cathode and separator materials arranged therein are provided. The housing of the battery cell is then filled with electrolyte (first electrolyte and subsequently second electrolyte) so that SEI and CEI layers can be formed during the formation process.
[0093] The addition of the electrolyte is carried out in particular as follows. An organic polymer (which has not yet been oxidized by potassium permanganate or sodium permanganate) is added as a component of the first electrolyte to the battery cell (i.e. the housing and the stack of anode, cathode and separator material arranged therein). The organic polymer comprises in particular at least an alcohol or an aldehyde. The organic polymer should be oxidizable by potassium permanganate or sodium permanganate, in particular at room temperature. After the addition of the organic polymer, the battery cell is appropriately treated to ensure that the organic polymer sufficiently contacts or wets the cathode and anode.
[0094] After wetting with the organic polymer, the formation process can begin. In this case, the battery cell is charged and discharged at a low C-rate of about 0.3C via an external power source.
[0095] Preferably, a significantly lower C-rate of about 0.1C is used and the cell is charged to a SOC (state of charge) of at least 1% and at most 10%. Before this SOC, lithium and electrolyte (almost) do not form a SEI. In particular, when the voltage values of the anode and cathode are too high, certain additives may be reduced or oxidized.
[0096] After reaching a specified SOC value of 1% to 6% SOC, as part of the second electrolyte addition, a solution containing a solvent (eg, acetonitrile) and potassium permanganate or sodium permanganate as a component of the second electrolyte is added to the battery cell.
[0097] The permanganate anions present in the solution now react in particular with the organic polymer (added as part of the first addition of electrolyte) and form oxidation products such as carboxylic acids and ketones. These oxidation products adhere to the active material of the cathode and / or the active material of the anode and form an organic layer there as a component of the CEI and SEI. This organic layer is formed before the lithium forms the inorganic layer.
[0098] Thus, in particular, two (different) electrolyte compositions are added to the battery cell at different times. In the context of the first electrolyte addition, in particular an electrolyte is added with an organic polymer as an additive. The organic polymers are selected such that they are (later) easily oxidized by permanganate anions.
[0099] In the second electrolyte addition category, a solution of a solvent (e.g. acetonitrile) and potassium or sodium permanganate (solute) is added to the cell, especially in the early stages of the formation process. As the organic polymer is oxidized by the permanganate anions, an organic layer is formed at both the anode and cathode.
[0100] Since the permanganate anions are consumed (at least for the most part, if necessary completely) during the formation of the organic layer formed by oxidation, in particular only potassium or sodium cations remain. These potassium or sodium cations move towards the anode. The potassium or sodium cations are too large for graphite (active material of the anode) and therefore cannot be inserted into the graphite. This can lead to potassium deposits on the anode surface. In order to avoid this, a mixture of graphite and hard carbon is used as the active material of the anode. In contrast to graphite, hard carbon has particularly large, randomly distributed voids into which potassium cations can be inserted and form covalent bonds with the carbon.
[0101] This intercalation occurs particularly at low C-rates, allowing the formation process to proceed at a low C-rate of 0.1 C. Potassium is retained by the hard carbon through intercalation and absorption (as shown below).
[0102] The potassium or sodium cations react, for example, with the fluoride of lithium hexafluorophosphate and form potassium fluoride or sodium fluoride. The inorganic ionic compound forms an inorganic layer on the anode side, in particular before the lithium-based inorganic layer is formed.
[0103] If some potassium or sodium cations are still bound in the hard carbon, they remain there even during operation of the battery at a higher C-rate or during further formation processes that occur at a higher C-rate. The hard carbon does not lose these cations even at higher C-rates (about 0.3C). The absorbed parts of the potassium or sodium cations cannot get out and remain inside the hard carbon. This means that the hard carbon with potassium or sodium ions acts as a rigid material and helps to compensate for the expansion of the graphite.
[0104] Potassium or sodium cations absorbed or inserted into the carbon can be used to form an inorganic potassium or sodium layer, especially with other halides such as bromide, chloride or fluoride. In this case, in addition to the lithium hexafluorophosphate salt in the electrolyte (which is a fluoride source), other salts such as lithium perchlorate (LiClO4) or lithium tetrafluoroborate (LiBF4) are added, for example in an amount of 0.1 to 0.2 moles. The halides of these lithium salts release halide anions, which can, for example, combine with potassium cations to form potassium fluoride, potassium chloride or potassium bromide. For example, lithium hexafluorophosphate can release fluoride anions, which can be used to form an inorganic potassium fluoride layer.
[0105] The inorganic compound forms an inorganic SEI layer on the anode before forming an inorganic layer with lithium. In this way, lithium will not be consumed during the formation of the SEI layer, and the capacity of the battery core will not be lost during the formation process.
[0106] Other oxidants may also be used to form the inorganic layer. For example, halides may be used in the context of a third electrolyte addition. For example, a solution of bromine in alcohol may be used. A source of fluoride gas may also be provided within the housing of the cell, such as in a gas reservoir, and then used to form an inorganic potassium fluoride or sodium fluoride layer by flowing the fluoride gas into the cell.
[0107] Compared with the known methods, the present invention has the following differences:
[0108] The battery cell is filled with electrolyte in at least two steps; in the context of the first electrolyte addition (first electrolyte), an easily oxidizable organic polymer is added as an additive; the battery cell then undergoes a (usual) wetting process so that the additives, including the remaining components of the first electrolyte, can penetrate into the active materials of the anode and cathode;
[0109] The formation of the battery cell is carried out (at least initially) at a low C-rate of about 0.1 C to a low SOC; within the scope of the second electrolyte addition (second electrolyte), potassium permanganate or sodium permanganate dissolved in an anhydrous organic solvent is added; for example, potassium permanganate is thus decomposed into potassium cations and permanganate anions;
[0110] The anode is composed of a mixture of graphite and hard carbon; for example, potassium ions can be deposited and absorbed in the irregular gaps of hard carbon due to the low C-rate;
[0111] The permanganate anions react with the easily oxidized organic polymers to form an organic layer composed mainly of carboxylic acids; the organic layer is formed on the cathode during the charging process; the organic layer is formed as a cathode-electrolyte interface (CEI), that is, by the strongly oxidizing permanganate anions, rather than by the high voltage applied to the cathode during the formation process; the organic layer prevents further oxidation of the electrolyte solvent; in addition, the inorganic layer formed later on the organic layer is not as strongly adhered, making the CEI layer thinner and the grain size smaller, increasing the mobility of lithium ions through the CEI;
[0112] During the discharge phase, the same permanganate anions form an organic layer on the anode, which helps to reduce the resistance of the SEI. The organic layers in the SEI and CEI result in lower ionic resistance.
[0113] For example, potassium cations react with halides (such as fluoride, bromide, and chloride) present in lithium salts to form inorganic potassium halide ion compounds; this forms an inorganic SEI layer before the inorganic SEI layer of lithium is formed;
[0114] To enhance the formation of this inorganic potassium halide layer, various salts such as lithium perchlorate (LiClO4) and lithium tetrafluoroborate (LiBF4) are added as electrolyte additives;
[0115] In the context of the third electrolyte addition, the halide can also be added during the formation process in the form of a bromohydrin solution or a fluoride gas, which is stored in a gas reservoir in the cell housing and then released into the cell during the formation process;
[0116] The above proposed multi-stage electrolyte addition produces organic and inorganic SEI and CEI layers before the SEI or CEI layer is formed from lithium and electrolyte solvent. The most important additive is potassium permanganate (or sodium permanganate) as an oxidant.
[0117] The method proposed by the present invention particularly achieves the following advantages:
[0118] The SEI produced according to the present invention allows for higher ion mobility because there are more grain boundaries due to the small grain size structure;
[0119] The SEI produced according to the present invention has higher adhesion, for example, it will not dissolve when vibrated;
[0120] The CEI produced according to the present invention has lower impedance; this results in faster ion movement;
[0121] Producing the SEI without requiring large amounts of additives in the electrolyte;
[0122] The irreversible loss of lithium ions during SEI formation is small because SEI and CEI are formed without reacting with lithium;
[0123] High efficiency in the formation process of the battery cell; because the formation process according to the invention forms high-quality SEI and CEI (high ion mobility, high adhesion, low impedance and low thickness due to a large number of grain boundaries);
[0124] The additives used, such as potassium permanganate solution, are non-toxic;
[0125] The main electrolyte solvent is not oxidized because the organic layer is formed by oxidizing the organic polymer with, for example, potassium permanganate;
[0126] Acetonitrile, used, for example, as a solvent for the preparation of potassium or sodium permanganate solutions, has good electrolyte properties in terms of viscosity and dielectric properties;
[0127] Additional lithium salts, such as lithium perchlorate (LiClO4) and lithium tetrafluoroborate (LiBF4), have good lithium mobility, thus further reducing the electrolyte's resistance to lithium ion migration;
[0128] Potassium or sodium inserted or absorbed in the hard carbon forms a rigid layer around the graphite, which helps reduce the swelling of the graphite; these potassium or sodium ions remain in the hard carbon during charge and discharge at higher C-rates; however, at lower C-rates, they can also migrate to the cathode, helping to increase the capacity of the battery cell;
[0129] Sodium permanganate can be used instead of or in addition to potassium permanganate; in this case, the sodium ions and optionally the potassium ions are inserted or absorbed into the hard carbon, thereby helping to give the battery cell additional capacity and forming an inorganic SEI layer of sodium or potassium halide ion compounds;
[0130] • Due to the absorption of free fluoride anions by potassium or sodium cations, less hydrofluoric acid (HF) is formed; this reduces the problem of outgassing of the battery cell during operation (ie the formation of gas inside the housing of the battery cell).
[0131] A battery cell is also proposed, which comprises at least a housing and a stack arranged therein, the stack comprising at least one cathode, an anode and a separator as well as a liquid electrolyte. The battery cell is produced by the method.
[0132] A motor vehicle is also proposed, which comprises at least a traction drive and a battery having at least one of the battery cells, the traction drive being able to be powered by the at least one battery cell.
[0133] The method can in particular be carried out by a control unit which is designed, configured or programmed to carry out the described method. With the control unit, at least the steps of the method can be carried out in an automated or partially automated manner.
[0134] Furthermore, the method may also be executed by a processor of a computer or a control unit.
[0135] Therefore, a system for data processing is also proposed, the system comprising a processor adapted / configured to perform the proposed method or a part of the steps of the method.
[0136] A computer-readable storage medium may be provided which includes instructions which, when executed by a computer / processor, cause it to perform at least a portion of the proposed method or steps.
[0137] The statements concerning the method can be transferred in particular to a battery cell, a motor vehicle, a control unit and a computer-implemented method (ie a computer or a processor, a system for data processing, a computer-readable storage medium) and vice versa.
[0138] The use of the indefinite article ("a"), especially in the claims and descriptions thereof, should be understood as this rather than a numerical word. Thus, the terms or components introduced accordingly should be understood as being present at least once, but in particular also as being present a plurality of times.
[0139] As a precaution, it should be noted that the numerals used here ("first", "second", etc.) are primarily (only) used to distinguish several similar objects, dimensions or processes, i.e., no dependency and / or order of these objects, dimensions or processes is mandatory. If dependency and / or order is required, it is explicitly stated in this document or is obvious to a person skilled in the art when studying the specifically described embodiments. If a component can appear multiple times ("at least one"), the description of one of these components may also apply to all or part of most of these components, but this is not mandatory. BRIEF DESCRIPTION OF THE DRAWINGS
[0140] The invention and the technical environment are explained in more detail below with reference to the accompanying drawings. It should be noted that the invention should not be limited to the exemplary embodiments cited. In particular, unless otherwise explicitly stated, partial aspects of the situations explained in the drawings can also be extracted and combined with other components and knowledge from the present description. It should be particularly noted that the drawings, in particular the size ratios shown, are only schematic. In the drawings:
[0141] Figure 1 An anode material having a SEI layer is shown;
[0142] Figure 2Step d0) of the method is shown;
[0143] Figure 3 shows a side view of a cross section of a battery cell;
[0144] Figure 4 shows the sequence of the method; and
[0145] Figure 5 Insertion and uptake of potassium cations are shown. DETAILED DESCRIPTION
[0146] Figure 1 An anode material 7 with a SEI layer 14, 16 is shown. The SEI 14, 16 is a three-dimensional boundary layer built around the active anode material 7 (e.g., graphite). Each crack in the anode material 7 establishes a new surface on which the SEI 14, 16 accumulates. These SEI accumulations increase the electrical resistance and also reduce the ionic conductivity in the battery cell. In this case, the SEI layer consists of heterogeneous compounds. The SEI near the active anode material 7 is mainly inorganic compounds 16, such as LiF, Li2O, lithium carbonate and lithium hydroxide. These are formed by the reaction of lithium cations (derived from lithium salts) with fluoride anions (derived from lithium salts) or oxygen (derived from trace water). Due to its dense layer, this (inorganic) part of the SEI has a higher resistance to ion movement. In the area close to the electrolyte (i.e., on the side of the SEI facing away from the active anode material), the SEI is mainly formed by organic compounds, for example, by the reaction products of solvents such as ethylene carbonate. These organic compounds react with HF acid and are then converted into an organic SEI layer over time.
[0147] During the charging process of the lithium-ion battery cell 1, the lithium ions must first migrate through the SEI 14, 16 before being deposited in the active anode material 7. The lithium ions move along the grain boundaries 17 of the SEI 14, 16 rather than through the particles 18 (grains). When the grain size of the lithium ions is larger, the lithium ions must travel a longer distance along the grain boundaries to move to another subsequent grain boundary. Any longer path for the lithium ions reduces the conductivity of the lithium ions, thereby increasing the internal resistance of the battery cell 1.
[0148] The SEI 14 , 16 produced by the proposed method allows for higher ion mobility since more grain boundaries 17 are present due to the small grain size structure (smaller particles 18 ).
[0149] Figure 2Step d0 of the method is shown. Prior to step d), permanganate anions 9 and cations 10, 11 are provided in step d0), wherein first a solvent 12 is provided (see left figure), and then at least potassium permanganate or sodium permanganate 19 is added to the solvent 12 (see middle figure) and mixed and dissolved (right figure). In the process, potassium permanganate or sodium permanganate 19 is converted into permanganate anions 9 and potassium or sodium cations 10, 11.
[0150] Figure 3 A battery cell 1 is shown. The battery cell 1 comprises a housing 4 and has at least one cathode material 6 (cathode), an anode material 7 (anode) and a separator material 8 (separator) arranged therebetween as well as a liquid electrolyte 2, 3 in the housing 4. The cathode 6, anode 7 and separator 8 are stacked on top of each other in a known manner.
[0151] Figure 4 The sequence of the method is shown. According to step a) 20 , a battery cell 1 is provided, which comprises a housing 4 and a stack 5 of cathode material 6 , anode material 7 and separator material 8 arranged therein.
[0152] According to step b) 21 , the housing 4 is at least partially filled with a first electrolyte 2 , wherein the first electrolyte 2 comprises at least an organic polymer.
[0153] According to step c) 22, the anode material 7 and the cathode material 6 are typically wetted by the first electrolyte 2. The aim here is to ensure that the anode and cathode materials 6, 7 are adequately acted upon by the first electrolyte 2.
[0154] Between steps c) 22 and d) 23, the battery cell 1 is connected to the external voltage source 13 and the formation process is started, the formation being carried out at a C-rate of at most 0.35C.
[0155] According to step d) 23 , when a predetermined state of charge is reached, the housing 4 is further filled with a second electrolyte 3 comprising at least permanganate anions 9 and potassium cations 10 or sodium cations 11 .
[0156] Permanganate anions 9 and cations 10, 11 are provided in step d0) 24 before step d) 23, wherein at least potassium permanganate 19 and / or sodium permanganate 19 are mixed and dissolved with a solvent 12. In this case, potassium permanganate or sodium permanganate 19 is converted into potassium permanganate anions 9 and potassium cations 10 or sodium cations 11.
[0157] After step d) 23, in step e) 25, a halide 26 is added to the electrolyte 2, 3 arranged in the housing 4. After step d), the cations 10, 11 react with (at least) one halide 26, resulting in the formation of an inorganic SEI layer 16 on the anode material 7.
[0158] Figure 5 The insertion and absorption of potassium cations 10 are shown. Since the permanganate anions 9 are consumed (at least largely, possibly completely) during the formation of the organic layers 14, 15 formed by oxidation, only potassium cations 10 remain. These potassium cations move towards the anode (anode material). The potassium cations 10 are too large for graphite 27 (active material of the anode 7) and therefore cannot be inserted into the graphite 27. This can result in potassium being deposited on the anode surface. To avoid this, a mixture of graphite and hard carbon is used for the active material of the anode. With graphite 27 ( Figure 5 In the upper right corner of the figure), compared with hard carbon 28 (see Figure 5 The lower two illustrations in the figure have larger randomly distributed cavities into which the potassium cation 10 can insert and form a covalent bond with the carbon.
[0159] This insertion occurs at a low C-rate, so the formation process can be carried out at a low C-rate of 0.1 C. Potassium is retained by the hard carbon 28 (e.g., Figure 5 lower right corner).
[0160] The potassium cation reacts with the fluoride of lithium hexafluorophosphate, for example, and forms potassium fluoride or sodium fluoride. The inorganic ionic compound forms an inorganic SEI layer on the anode material before forming the lithium-based inorganic layer.
[0161] If some potassium cations 10 are still incorporated in the hard carbon 28, they will remain there even during operation of the battery at a higher C-rate or during further formation processes occurring at a higher C-rate. Even at a higher C-rate (about 0.3C), the hard carbon 28 does not lose these cations 10. The absorbed portion of the potassium cations 10 cannot come out and remains inside the hard carbon 28. This means that the hard carbon 28 with potassium ions 10 acts as a rigid material, helping to compensate for the expansion of the graphite 27.
[0162] Potassium cations 10 absorbed or inserted in carbon (hard carbon 28) can be used to form an inorganic potassium layer (inorganic SEI layer 16), especially together with other halides 26 such as bromide, chloride or fluoride. In this case, in addition to the lithium hexafluorophosphate salt in the electrolyte 2, 3 (which is a fluoride source), other salts such as lithium perchlorate or lithium tetrafluoroborate are added. The halides 26 of these lithium salts release halogenated anions, and these anions can, for example, combine with potassium cations 10 to form potassium fluoride, potassium chloride or potassium bromide.
[0163] These inorganic compounds form an inorganic SEI layer on the anode material before forming an inorganic layer with lithium. In this way, no lithium is consumed during the formation of the SEI layer, and the capacity of the battery cell is not lost during the formation process.
[0164] List of Reference Numerals
[0165] 1 battery cell
[0166] 2. First Electrolyte
[0167] 3. Second electrolyte
[0168] 4 Shell
[0169] 5 stacks
[0170] 6. Cathode Materials
[0171] 7 Anode material
[0172] 8. Diaphragm material
[0173] 9 Permanganate anion
[0174] 10 Potassium cation
[0175] 11 Sodium cation
[0176] 12 Solvents
[0177] 13 Voltage Source
[0178] 14 Organic SEI layer
[0179] 15Organic CEI layer
[0180] 16Inorganic SEI layer
[0181] 17 Grain Boundary
[0182] 18 pellets
[0183] 19 Potassium permanganate or sodium permanganate
[0184] 20. Step a) of the method
[0185] 21. Step b) of the method
[0186] 22. Step c) of the method
[0187] 23. Step d) of the method
[0188] 24. Step d0 of the method
[0189] 25. Step e) of the method
[0190] 26 Halides
[0191] 27 Graphite
[0192] 28 Hard Carbon
[0193] 29 Inserted cation
[0194] 30 absorbed cations
Claims
1. A method for manufacturing a battery cell (1), wherein: The battery cell (1) comprises a housing (4) filled with an electrolyte (2, 3) and a stack (5) arranged in the housing and consisting of a cathode material (6), an anode material (7) and a separator material (8); wherein the method comprises at least the following steps: a) providing a battery cell (1), the battery cell comprising a housing (4) and a stack (5) arranged in the housing and consisting of a cathode material (6), an anode material (7) and a separator material (8); b) at least partially filling the housing (4) with a first electrolyte (2), wherein the first electrolyte (2) comprises at least an organic polymer; and subsequently c) wetting the anode material (7) and the cathode material (6) with the first electrolyte (2); and then d) further filling the housing (4) with a second electrolyte (3) comprising at least permanganate anions (9).
2. The method according to claim 1, wherein: The second electrolyte (3) contains at least potassium cations (10) and sodium cations (11).
3. The method according to claim 2, wherein: In step d0) prior to step d), the permanganate anions (9) and cations (10, 11) are provided, wherein at least potassium permanganate (19) or sodium permanganate (19) is mixed with a solvent (12) and dissolved.
4. The method according to claim 3, wherein: The solvent (12) contains at least acetonitrile.
5. A method according to any one of the preceding claims, wherein: Between steps c) and d), the battery cell (1) is connected to an external voltage source (13) and the formation process is started, wherein the formation is carried out at a C-rate of at most 0.35C.
6. The method according to claim 5, wherein: Step d) is only performed when the battery cell (1) has reached a state of charge of at least 1% and at most 10%.
7. A method according to any one of the preceding claims 5 or 6, wherein: Only after step d) does the C-rate increase to a higher value of at least more than 0.3C.
8. A method according to any one of the preceding claims, wherein: The active material of the anode material (7) includes at least graphite (27) and hard carbon (28).
9. A method according to any one of the preceding claims, wherein: After step d), the permanganate anions (9) react with the organic polymer and thereby form an organic SEI layer (14) on the anode material (7), and an organic CEI layer (15) on the cathode material (6), and wherein the cations (10, 11) react with the halide (26) and thereby form an inorganic SEI layer (16) on the anode material (7).
10. The method according to claim 9, wherein: After step d), in step e), a halide (26) is added to the electrolyte (2, 3) arranged in the housing (4).
Citation Information
Patent Citations
Alkali Metal-Sulfur Secondary Battery Containing a Nano Sulfur-Loaded Cathode and Manufacturing Method
US20180233784A1